Geotourism: Use of Environmentally Friendly Geological Wealth: Field Study of Kayangan Api, Mystical Tourism for the Traces of Empu Supo in Bojonegoro - Hakimah, Nurul Lathifatul; Sanjaya, I Gusti Made; Hariyono, Eko; Kodir, Abdul (Indonesia Approach Education, 2023)
The writing of this article examines how solutions using geology can be cultivated in the management of historical sites as community ecotourism and community economic activities. The geotourism management paradigm is how tourism management can optimize the natural potential (geology) to add value to the economic well-being of local people living in the Kayangan Api area and minimize potential natural damage in Kayangan Api environment. The method used in this study is Kayangan Api tourist observation, expert interviews (guards) and literacy surveys. Therefore, this paper proposes a tourism management model. Geotourism management is grouped under five main focuses, including the formulation of natural opportunities used in tourism activities, the description of criteria for geotourism sites (Kayangan Api), the management of geotourism (Kayangan Api), and the explanation of geotourism activities and finally the indicators of success or Kayangan Api Bojonegoro Geotourism Print.